Good teaching practice for virtual classroom design in Google Classroom - Gómez Goitia, Jose Manuel (2020)
Google Classroom is a tool that allows to manage educational processes in an agile and easy way, allowing to create classes, assign homework, grade, send comments and give access to the entire educational process in one place. The objective was the analysis of the incidence of Google Classroom in the pedagogical management in the participants of the Master in Education of the Universidad Tecnológica Indoamérica. As a conclusion, its use shown advantages for the students, who were very participative and demonstrated a high level of immersion in the virtual environment, from the use of different collaborative work tools.